2007
DOI: 10.1002/ijc.22614
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, physical activity and the risk of pancreatic cancer in a large Japanese cohort

Abstract: It is unclear whether body mass index (BMI) and physical activity are associated with the risk of pancreatic cancer in Asian populations. We examined these associations in the Japanese Collaborative Cohort Study for Evaluation of Cancer Risk. Our cohort study included 110,792 Japanese men and women at enrollment (1988)(1989)(1990). Data on height, body weight (at baseline and at age 20 years) and physical activity were obtained from a questionnaire. Cox proportional hazards models were used to estimate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 52 publications
(67 reference statements)
1
46
2
3
Order By: Relevance
“…In so doing, comparability between studies would be improved that would permit better assessments across populations. Although we found a non-statistically significant risk reduction among the 9 studies reporting LTPA corresponding to WHO recommendations (8,18,21,22,25,41), this finding may be attributable to the moderately high heterogeneity among these studies. An important risk reduction may be present in these studies that could be more fully assessed with a pooled analysis that would apply a common definition for LTPA across studies.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In so doing, comparability between studies would be improved that would permit better assessments across populations. Although we found a non-statistically significant risk reduction among the 9 studies reporting LTPA corresponding to WHO recommendations (8,18,21,22,25,41), this finding may be attributable to the moderately high heterogeneity among these studies. An important risk reduction may be present in these studies that could be more fully assessed with a pooled analysis that would apply a common definition for LTPA across studies.…”
Section: Discussioncontrasting
confidence: 72%
“…1). Of these 26 studies, 7 reported men and women as separate populations (6,18,22,33,(41)(42)(43); therefore, 33 risk estimates were accounted for in the overall analysis.…”
Section: Summary Of Literature Searchmentioning
confidence: 99%
“…A recent study in Lancet (2012), adds evidence to these estimates with its report that physical inactivity in UK attributed to a further increase risks of about 18 percent breast cancers and 19 percent of colon cancers. Nevertheless, some studies have shown a risk reduction (Hanley et al, 2001;Michaud et al, 2001), yet other studies does not even show an association (Patel et al, 2005;Lin et al, 2007). For example, a recent meta-analysis showed leisure time physical activity (LTPA) has no association on risk of pancreatic cancer (Bao and Michaud, 2008), highlighting that the type of cancer is an influential factor.…”
Section: Physical Activity and Quality Of Life Of Cancer Survivors: Amentioning
confidence: 99%
“…(3)(4)(5)(6)(7) The effect of alcohol consumption on risk has also been investigated in many casecontrol or cohort studies, but results have been inconsistent. (7)(8)(9)(10)(11)(12)(13)(14) In many studies, the impact of alcohol disappeared after adjustment for potential confounders, particularly smoking habits, (12)(13)(14) while several groups found a significant impact of alcohol even after adjustment for confounders.…”
mentioning
confidence: 99%